Community Socio-Cognitive Characteristics and Perceptions of Inclusive Education - Firmanto, Ari; Sumarsono, Puji; Nur, Fitria (KnE Social Sciences, 2025)
This study investigates the correlation between the socio-cognitive characteristics of a community and their understanding of inclusive education. The community’s comprehension of special needs and their awareness of the importance of inclusive education are positively correlated with their inclusive perspectives. This study uses a quantitative methodology, with a sample drawn from diverse social groups (age groups, educational backgrounds, socioeconomic levels) as well as community members involved in educational contexts (parents, teachers, school administrators). Data were collected through surveys, interviews, observations, and relevant document analysis and were analyzed using descriptive statistical techniques to identify relevant patterns, trends, and findings. The results indicate that the socio-cognitive characteristics of a community play a significant role in understanding and implementing inclusive concepts in education. Various social groups within the community contribute diverse perspectives to the understanding and support of inclusive education. These findings highlight the importance of engaging all levels of society in efforts to create inclusive educational environments. This study offers valuable insights for educational stakeholders, including teachers, school staff, educational policymakers, and the broader community.